The big secret - Pearl, Alexa, 1967- (Pearl, Alexa, 1967- Tales of Sasha, 2017)
"In the Tales of Sasha series debut, Sasha discovers that she really isn't like the other horses in her valley when wings sprout from her back and she soars through the air!"--